2021
DOI: 10.3389/fphar.2020.539261
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropyridine Calcium Channel Blockers Suppress the Transcription of PD-L1 by Inhibiting the Activation of STAT1

Abstract: Programmed death ligand 1 (PD-L1) which is upregulated in various epithelial tumors, plays a central role in the evasion of the immune system. In addition to monoclonal antibodies that blocking PD1/PD-L1 axis, finding small molecule compounds that can suppress PD-L1 expression might be another substitutable strategy for PD1/PD-L1 based therapy. Here, we found that dihydropyridine calcium channel blockers dose-dependently reduced the expression of PD-L1, both in the cytoplasm and cell surface. IFNγ induced PD-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Mechanistically, elesclomol forms an elesclomol-Cu (II) complex by chelating copper (Cu) outside of cells, which rapidly transports copper into the mitochondria, thus inducing mitochondrial ROS accumulation [ 472 , 473 ]. Other types of metal chelators, including zinc and calcium chelating agents, have also been recognized as effective antitumor agents [ 474 , 475 ].…”
Section: Strategies For Overcoming Mitochondria-targeting Bottlenecks...mentioning
confidence: 99%
“…Mechanistically, elesclomol forms an elesclomol-Cu (II) complex by chelating copper (Cu) outside of cells, which rapidly transports copper into the mitochondria, thus inducing mitochondrial ROS accumulation [ 472 , 473 ]. Other types of metal chelators, including zinc and calcium chelating agents, have also been recognized as effective antitumor agents [ 474 , 475 ].…”
Section: Strategies For Overcoming Mitochondria-targeting Bottlenecks...mentioning
confidence: 99%
“…Immunotherapies are also on the rise in cancer treatment. One study found that blocking calcium channels can suppress the transcription of programmed death-ligand 1 (PD-L1) and enhance natural killers cells’ ability to eliminate the cancer [ 88 ]. Chemotherapies that target calcium signaling, similar to those used against breast cancer, such as cisplatin and doxorubicin, were found to be synergistic in combination with EGFR inhibitors (gefitinib and erlotinib) and to prolong patient survival in the clinic [ 89 ].…”
Section: Combination Therapymentioning
confidence: 99%
“…This has been demonstrated with the CCB lercanidipine that is capable of down-regulating PD-L1 in lung cancer cells (NCI-H1299 cells and NCI-H460 cells) and enhancing the killing ability of T cells. A similar capacity to induce T cell-mediated cancer cell death was then evidenced with azelnidipine and amlodipine, although these two other CCBs were slightly less potent than lercanidipine [ 64 ] ( Figure 3 b). In another similar study, amlodipine was found to induce of PD-L1 degradation and antitumor immunity in a mouse MC38 tumor model.…”
Section: Drug Repositioning To Target the Pd-1/pd-l1 Checkpointmentioning
confidence: 70%